School Nurse-Parent Partnership in School Health Care for Children with Type 1 Diabetes: A Hybrid Method Concept Analysis - Ju-Yeon Uhm; Mi-Young Choi (Elsevier, 2022)
Summary: Purpose: To define school nurse-parent partnerships in school health care for children with type 1 diabetes (T1D) and determine its attributes using a hybrid model. Methods: This method involves a three-phase process: theoretical, fieldwork, and analytical. A literature review was conducted during the theoretical phase. A literature search of articles from January 1991 to February 2020 was conducted using relevant electronic databases. Eighty-three articles that met the inclusion criteria were completely read. Fieldwork data were collected through individual interviews from February to July 2019 in South Korea. In the fieldwork phase, interviews were conducted individually with 22 mothers of students with T1D and 20 school nurses recruited by purposeful sampling. Inductive content analysis was conducted. The findings from the theoretical phase were integrated with those from the fieldwork phase, and the final concept was derived. Results: School nurse-parent partnership in school health care for children with T1D has been defined as an interactive process of maintaining a balanced responsibility and providing tailored care to meet needs by establishing trusting relationships and communicating transparently and openly. This analysis yielded four attributes: trusting relationships, transparent and open communication, balanced responsibility, and providing tailored care to meet needs-this entails providing nursing actions by advocating for students and performing a negotiated role together or individually for student and family. Conclusion: The findings of this study add to the importance of an attribute of balancing responsibility for partnership in school health care. The results show that this partnership could contribute to the development of a scale, theory, and nursing intervention in school health care for children with T1D.